Pengembangan Lanjut Web E-Learning Codemaniac menggunakan Web Adaptif berbasis Log: Pengembangan Lanjut Web E-Learning Codemaniac Menggunakan Web Adaptif Berbasis Log - Achmad Hanim Nur Wahid; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Education is one of the most important needs for human civilization, especially for children and teenagers. The current pandemic condition is forcing education to use online learning alternatives. Codemaniac is one of the e-learning which is builded using gamification techniques to increase student motivation. However, Codemaniac does not yet have adaptive features that can maximize the behavior of each user. To overcome this problem, further development of Codemaniac will add adaptive features by utilizing the recorded user behavior contained in the log file. Based on the recorded user behavior, clustering will be carried out using the fuzzy c-means algorithm so that three types of clusters will be formed, each cluster will present a different user interface. This system is compiled using SDLC waterfall with the addition of the Python programming language. In its development, it produces 3 actors, with an additional 5 functional requirements and 1 non-functional requirement. To test the system, the wthite box method is used for unit testing and the black box method is used for validation testing.